PSX-24 Effect of compound organic trace minerals on growth performance, serum indices and micromineral excretion in fattening pigs. (7th December 2018) - Ma, L; He, J; Hou, C; Qiu, J; Lu, X; Liu, B; Lin, G; Xue, Y; Koontz, A; Yu, D
Abstract: The effects of low-dose organic trace minerals in fattening pigs were evaluated using 192 Duroc x Landrace x Large White pigs with similar body mass (61.2 ± 4.4 kg) and identical parity. Pigs were divided into four groups with four replicate pens per group (12 pigs per pen) in a 2 x 2 factorial design. Factors were background mineral source and finishing phase mineral source. Background minerals were fed as either I (commercial dosages of inorganic Fe, Cu, Mn, Zn) or O (organic Fe, Cu, Mn, Zn at 50%, 30% and 20% commercial levels during suckling, nursing, and growing phases respectively; Bioplex®, Alltech Inc., Nicholasville, KY, USA). During the finishing phase treatments were ITM (basal diet＋inorganic Fe, Cu, Mn, Zn at 100, 20, 25, 100 mg/kg, respectively) and OTM (basal diet＋ Bioplex® Fe, Cu, Mn, Zn of 20, 4, 5, 20 mg/kg, respectively). The finishing period lasted 82 days, with two stages (38 days early finishing and 44 days late finishing). Neither background or finishing treatment had significant influence on finishing phase performance (P>0.05). Serum Zn and Mn-SOD activity were higher (P ≤ 0.05) in OTM pigs during the early finishing stage, while MDA content was lower (P=0.05). OTM significantly reduced the Fe, Mn, Cu and Zn levels (P < 0.05) in manure during both finishing phases, while O significantly decreased (P < 0.05) fecal Fe content in the early finishing stage and fecal Cu and Zn contents in the late finishing stage. O and OTM interacted (P < 0.05) to further reduce fecal Fe content during the late finishing stage. Both low dose organic trace mineral feeding during early growth stages or finishing reduced the micromineral excretion in manure without affecting growth performance of fattening pigs, while feeding during finishing improved antioxidant levels of fattening pigs.